Election-year stimuli and economic performance: Evidence from a macroeconometric model of the Philippines - Mark Gerald C. Ruiz; Ramona Maria L. Miral; John Paolo R. Rivera (Philippine Institute for Development Studies (PIDS), 2025)
We evaluated the transmission of election shocks in the Philippine economy using an augmented macroeconometric model that integrates political business cycle (PBC) dynamics into the country's macroeconomic framework. Building upon the model developed by Debuque-Gonzales and Corpus (2023, 2024), quarterly data from 2002 to 2023 were utilized to simulate the effects of election-induced fiscal and private sector behavior on key macroeconomic variables, namely private consumption, employment, investment, and government consumption. Results reveal that election years generate short-term, demanddriven expansions, fueled by heightened government spending, campaign activities, and temporary job creation. However, these effects are transitory, with economic activity reverting near baseline levels post-election as fiscal impulses fade. Findings align with established literature on political budget cycles, confirming that election-driven growth is cyclical rather than structural, and may induce inefficiencies in expenditure allocation and fiscal discipline. The study highlights the need for institutional reforms, fiscal transparency, and counter-cyclical policies to mitigate volatility and promote long-term stability. Finally, limitations related to model stability, pandemic disruptions, and evolving post-COVID economic structures suggest avenues for recalibrating and rewriting the macroeconometric model for future applications.
Keywords: C51; E62; 330; election shocks; macroeconometric modeling; political business cycles